Zinc Oxide Nanoparticles-Enriched Extender Enhances Cryosurvival and Antioxidant Defense of Buffalo Spermatozoa - Patel, Richakumari M; Parmar, Kirankumar H; Chaudhari, Meet T; Chaudhari, Dinesh V; Pathan, Mohsin M; Parmar, Jignesh J (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study was conducted at the Central Sperm Station of the College of Veterinary Science in Anand, to evaluate the effect of zinc oxide nanoparticles (ZnONPs) on the post-thaw quality of buffalo bull semen. A total 18 ejaculates from four mature healthy breeding bulls were collected using an artificial vagina and evaluated for semen quality. Semen samples showing >70% initial motility were diluted in Tris fructose egg yolk glycerol (TFYG) extender, divided into four aliquots supplemented with 0 (control), 10, 25, and 50 µg/mL ZnONPs, equilibrated at 4°C, frozen in liquid nitrogen vapour, and stored at -196 °C overnight. Post-thaw semen was evaluated for sperm motility, viability, morphology, acrosome integrity, plasma membrane integrity (HOST), lipid peroxidation (MDA), and total antioxidant capacity (TAC). Statistical analysis revealed that a significant (p<0.05) improvement was observed in post-thaw sperm motility, viability, plasma membrane and acrosome integrity, and antioxidant activity in ZnONPs-supplemented groups compared to the control. The 25 µg/mL ZnONPs concentration showed the most significant enhancement (p<0.05) in sperm quality parameters, accompanied by a significant reduction (p<0.05) in lipid peroxidation levels and an increase in total antioxidant capacity, indicating optimal protection against oxidative damage, followed by 10 µg/mL, while higher concentration (50 µg/mL) showed a detrimental effect.